The bosses' union : how employers organized to fight labor before the New Deal - Hulden, Vilja, 1977- (Working class in American history., 2023)
"From the 1880s through the 1920s, American labor endured an ongoing assault on worker's rights by open shop campaigns organized by employers. Vilja Hulden delves into the decades-long effort to not only counter but discredit labor's attempts to exercise its own power. The employer-invented term closed shop was a potent rhetorical tool that shifted public opinion from concerns about inequality and dangerous working conditions to a belief that unions trampled an individual's right to work. As Hulden shows, employers used different methods to conduct closed-shop campaigns. Conciliators assumed a pose of benevolent cooperation while hardliners like the National Association of Manufacturers condemned the closed shop and used financial and social networks to lobby government, purchase newspaper space, and place sympathizers in politics. Employers did not always get what they wanted. But their superior ability to exercise power strengthened an anti-labor agenda that showed a remarkable consistency in its tactics and goals over a fifty-year period"--